Desafios para uma educação emancipatória - Mattos, Rejane Maria Cunha (2014)
The present work of dissertation, Challenges for Emancipatory Education, is part of the Management, Education and Public Policies research field. It aims at examining and deepening the working students formation issue, checking whether they have experienced social emancipation process with new possibilities of professional insertion from technical school. This study basically comprehends two major subjects in its structure: firstly it introduces labor sources, its elementary concepts and the historic aspects of professional Education in Brazil. Having closed this first part, different understanding about social emancipation under the perspective of different thinkers are taken in consideration. The second moment of the present study includes methodological procedures which were taken for qualitative research to be carried out, information and data gotten by the students who came from Environment and Bibliotechonomy technical school out of understanding which working students come to about the professional activity they perform, in the social environment where they live.